Morphological diversity exploration of regional peppers in Yaxcaba, Yucatan, Mexico. - Latournerie, Luis (2006)
The main objective of this work was to know the types diversity and uses of the pepper, selection criteria and to get samples samples of the landraces. The studied system was a multi-cropping system with corn, beans, pepper and pumpkin (milpa), established in two stages: a) a survey on 60 land-owners from the community, in order to gather information of the crop and their croppin systems applied in the ‘milpa’, pach pakal (land useful for gardening) and back-yards. b) An etnobotanical exploration to collect genetic material and to conduct an in situ assessment of the morphological characters of the plant, fruit and flower. Eight regional pepper types are grown in the community, seven belong to the Capsicum annuum such (yaax ic, xcat’ic, cha’hua, chile dulce, sucurre, pico paloma and maax, the latter C. annuum var. aviculare and one C. chinense (habanero). The yaax ic pepper is the most widely accepted in the community. The farmers base their germplasm selection on the fruit size, taste, pests and disease tolerance and culinary uses. The regional peppers are planted in association with other crops in the “milpas” as well as in the back-yards.